The Use Of Mind Mapping Media To Improve Students' Writing Ability In Report Text At The Ninth Grade Of SMP Negeri 8 Pematangsiantar - Pardede, Gabriella; Selviana Napitupulu (Journal Innovative Practices in Education (JIPE), 2025)
Writing is one of the essential skills that students must master in learning English, as it enables them to express ideas and convey information effectively. However, many junior high school students still find it difficult to organize their thoughts and develop coherent report texts. This gap between the importance of writing and students' actual performance highlights the need for effective learning media. This study aims to improve students' writing ability in report text through the use of mind mapping media at the ninth grade of SMP Negeri 8 Pematangsiantar. The research was conducted using classroom action research (CAR) in two cycles, each consisting of planning, action, observation, and reflection. The subjects of the research were 30 students of class IX-3. The data were collected through writing tests, observation sheets, and field notes. The results of the study showed that the students' writing ability improved significantly after the implementation of mind mapping media. The improvement could be seen in the students' ability to generate ideas, organize paragraphs, and use correct grammar and vocabulary in writing report texts. The mean score of students' writing increased from 63.4 in the pre-test to 81.2 in the post-test of the second cycle. It can be concluded that mind mapping media effectively enhances students' writing ability in report text. Therefore, teachers are encouraged to use mind mapping as an alternative learning tool to make writing activities more structured, engaging, and easier for students to understand.